Agronomic, nutritional and physical characteristics of some Indian groundnut cultivars - MISRA, J B; GHOSH, P K; DAYAL, D; MATHUR, R S (The Indian Journal of Agricultural Sciences, 2013)
Â A study was conducted during 1995-97,2 winter and 2 rainy seasons on 18 groundnut culivars to evalutate their worthiness for export. Kernel yield along with observations on physical and chemical attributes of kernels was recorded. The physical attibutes studied were sound-mature kernels, shape of kernels, seed size uniformity, 100 seed-mass and colour of testa, while among the chemical attributes ubckkuded were oil, protein,sucrose, reducing sugar, and free amino acid co9ntents. The oil was analyzed for its fatty acid composition.The cultivars were finally evaluated on the basis of the relative desirability of various physical and chemical traits vis-a-vis kernel yield. Cultivar’ICGS 76’ ranked first in kernel yield, fifth for physical attributes and fourth for chemical attributes, and was thus identified as the most suitable cultivar for the hand picked and selected trade. Cultivars’ICGS 44’ and ’ICGS 11’ whichÂ bothÂ Â significantly higher than average kernel yields were adjudged to be high yielding cultivars with moderate physical and chemical attributes."TGK 19A’ an average yielder was adjudged to be the best for physical and chemical attributes and was followed by ’ICGS 11’ in the same category. Although the pouplar cultivar ’GG2’ gave significantly above average yield it ranked low in physical and chemical attributes.